The Form of Code Choice in Ganjar Pranowo Social Media Twitter - Isnaini, Faridha; Mardikantoro, Hari Bakti (Pascasarjana Universitas Negeri Semarang)
The choice of code used by Ganjar Pranowo to interact with citizens was varied according to the purpose and situation of the speech. The purpose of this study was to analyze the choice form of Ganjar Pranowo's speech code on Twitter social media. The data in this study were captured through the method of observation with the tapping technique as a basic technique, then the advanced technique consisted of a competent free interview and note taking technique. Data analysis was performed using the match method and distribution method. Based on the results of data analysis, the form of speech code selection used by Ganjar Pranowo on social media Twitter in the form of a single code, code switching, and code mixing.